2017
DOI: 10.1139/cjfas-2016-0381
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of acceptable biological catch (ABC) harvest control rules designed to limit overfishing

Abstract: In this paper we developed a simulation model to evaluate a range of acceptable biological catch (ABC) control rules to determine their relative performance at achieving common fishery management objectives. We explored a range of scenarios to determine robustness of a control rule to different situations and found that across scenarios the control rules that used a buffer to account for scientific uncertainty when setting the ABC were able to limit the frequency of overfishing. Modest buffers when setting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 30 publications
9
42
0
Order By: Relevance
“…The approach we propose could be used to evaluate how alternative levels of precaution would affect management choices. For example, Wiedenmann et al (2017) evaluated several alternative levels of precaution for the Mid-Atlantic Fishery Management Council's harvest control rule and found that the effects of adopting more precaution differed among life history and data quality scenarios. We believe that the precaution levels in our analyses are more intuitive with respect to what they are attempting to achieve than those of other approaches to calculating precautionary reference points.…”
Section: Discussionmentioning
confidence: 99%
“…The approach we propose could be used to evaluate how alternative levels of precaution would affect management choices. For example, Wiedenmann et al (2017) evaluated several alternative levels of precaution for the Mid-Atlantic Fishery Management Council's harvest control rule and found that the effects of adopting more precaution differed among life history and data quality scenarios. We believe that the precaution levels in our analyses are more intuitive with respect to what they are attempting to achieve than those of other approaches to calculating precautionary reference points.…”
Section: Discussionmentioning
confidence: 99%
“…Most stock assessments likely underestimate the uncertainty inherent in OFL estimates (Ralston et al 2011), and this negatively impacts the performance of many of the control rules used to manage fisheries (Wiedenmann et al 2017;Punt et al 2018). This variability means that estimates of OFL should really be considered probability distributions around the true point estimate.…”
Section: Catch Levels and Rebuildingmentioning
confidence: 99%
“…This variability means that estimates of OFL should really be considered probability distributions around the true point estimate. Most stock assessments likely underestimate the uncertainty inherent in OFL estimates (Ralston et al 2011), and this negatively impacts the performance of many of the control rules used to manage fisheries (Wiedenmann et al 2017;Punt et al 2018). NMFS revised the guidelines for National Standard 1 (74 FR 3178; 81 FR 7185873) in 2009 and again in 2016 to provide guidance to SSCs and the RFMCs on how the inherent management and scientific uncertainty should be incorporated into establishing annual catch limits (OFLs, ABCs, and ACLs) and associated accountability measures.…”
Section: Catch Levels and Rebuildingmentioning
confidence: 99%
“…This variability means that estimates of OFL should really be considered probability distributions around the true point estimate. Most stock assessments likely underestimate the uncertainty inherent in OFL estimates (Ralston et al 2011 ), and this negatively impacts the performance of many of the control rules used to manage fi sheries (Wiedenmann et al 2017 ;Punt et al 2018 ). NMFS revised the guidelines for National Standard 1 (74 FR 3178;81 FR 7185873) in 2009 and again in 2016 to provide guidance to SSCs and the RFMCs on how the inherent management and scientifi c uncertainty should be incorporated into establishing annual catch limits (OFLs, ABCs, and ACLs) and associated accountability measures.…”
Section: Catch Levels and Rebuildingmentioning
confidence: 99%